Infection with a Brazilian isolate of Zika virus generates RIG‐I stimulatory RNA and the viral NS5 protein blocks type I IFN induction and signalling - Hertzog, J; Dias, A; Rigby, R; Donald, C; Mayer, A; Sezgin, E; Song, C; Jin, B; Hublitz, P; Eggeling, C; Kohl, A; Rehwinkel, J (Wiley, 2018)
Zika virus (ZIKV) is a major public health concern in the Americas. We report that ZIKV infection and RNA extracted from ZIKV infected cells potently activated the induction of type I interferons (IFNs). This effect was fully dependent on the mitochondrial antiviral signalling protein (MAVS), implicating RIG‐I‐like receptors (RLRs) as upstream sensors of viral RNA. Indeed, RIG‐I and the related RNA sensor MDA5 contributed to type I IFN induction in response to RNA from infected cells. We found that ZIKV NS5 from a recent Brazilian isolate blocked type I IFN induction downstream of RLRs and also inhibited type I IFN receptor (IFNAR) signalling. We defined the ZIKV NS5 nuclear localization signal and report that NS5 nuclear localization was not required for inhibition of signalling downstream of IFNAR. Mechanistically, NS5 blocked IFNAR signalling by both leading to reduced levels of STAT2 and by blocking phosphorylation of STAT1, two transcription factors activated by type I IFNs. Taken together, our observations suggest that ZIKV infection induces a type I IFN response via RLRs and that ZIKV interferes with this response by blocking signalling downstream of RLRs and IFNAR.